Dirāsah Muqāranah li Natījah al-Ta‘allum fī ‘Ilm al-Naḥw baina Ṭalabah Barnāmij al-I‘dād al-Lugawī fī Jâmi‘At Magfirah wa Jâmi‘At Al-Râyah: Dirâsah Muqâranah bi Manhaj Kammiy: دراسة مقارنة لنتيجة التعلم في علم النحو بين طلبة برنامج الإعداد اللغوي في جامعة مغفرة وجامعة الراية دراسة مقارنة بمنهج كمي - Adi Budiman (Ukazh : Journal of Arabic Studies, 2026)
This study investigates significant differences in grammatical achievement between language preparation students at Maghfirah  (STIPI) and Istitut Muslim Cendikia (IMC), Indonesia and explain the reasons for the differences in learning outcomes between the two. This research a quantitative approach, a sample of 110 students (56 from STIPI and 54 from IMC) was selected through purposive. Data were collected via a 31-item objective achievement test, which demonstrated high reliability. Due to non-normal distribution, the Mann-Whitney U test was employed for analysis using SPSS. The results revealed a statistically significant difference (Sig = 0.000) favoring IMC with an average to large effect size of r = 0.399. IMC students achieved a high mean score of 84,40, while STIPI students scored 69.00. This disparity is attributed to two primary factors: academic, namely higher weekly study hours at IMC (4-5 hours) compared to STIPI (2-3 hours); and environmental, specifically IMC’s "complete linguistic isolation" and strict discipline versus "linguistic interference" from Indonesian at STIPI. The study recommends strengthening the langauge environment, reducing reliance on intermediary languages, and increasing instructional hours for core subjects. Future research should qualitatively investigate curriculum content and psychological variables influencing these varying achievement levels.